Development of Electrochemical Sensors/Biosensors to Detect Natural and Synthetic Compounds Related to Agroalimentary, Environmental and Health Systems in Argentina: A Review of the Last Decade - Granero, Adrian Marcelo (2021)
Electrochemical sensors and biosensors are analytical tools, which are in continuous development with the aim of generating new analytical devices which are more reliable, cheaper, faster, sensitive, selective, and robust than others. In matrices related to agroalimentary, environmental, or health systems, natural or synthetic compounds occur which fulfil specific roles; some of them (such as mycotoxins or herbicides) may possess harmful properties, and others (such as antioxidants) beneficial ones. This imposes a challenge to develop new tools and analytical methodologies for their detection and quantification. This review summarises different aspects related to the development of electrochemical sensors and biosensors carried out in Argentina in the last ten years for application in agroalimentary, environmental, and health fields. The discussion focuses on the construction and development of electroanalytical methodologies for the determination of mycotoxins, herbicides, and natural and synthetic antioxidants. Studies based on the use of different electrode materials modified with micro/nanostructures, functional groups, and biomolecules, complemented by the use of chemometric tools, are explored. Results of the latest reports from research groups in Argentina are presented. The main goals are highlighted.